1990
DOI: 10.1002/1097-0142(19900515)65:10<2295::aid-cncr2820651022>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Synovial sarcoma a DNA flow cytometric study

Abstract: The relationship between DNA content, clinicopathologic findings, and patient survival in synovial sarcoma was investigated. Patient age at diagnosis (P less than 0.001), tumor size (P less than 0.001), and ploidy status (P less than 0.003) correlated significantly with patient survival. A marginally significant correlation between mitotic count and patient survival was also observed (P = 0.04). Histologic subtypes (monophasic versus biphasic), mitotic count, and S-phase by flow cytometry had no significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 22 publications
3
27
2
Order By: Relevance
“…In our case also, keeping in view the extensive morbidity of surgery, chemoradiation was the treatment resorted to. There are reports in literature, which support the chemotherapy as successful mode of treatment [14,15]. Besides having some radiation mucositis the patient is doing fi ne after ten months of treatment.…”
Section: Discussionmentioning
confidence: 89%
“…In our case also, keeping in view the extensive morbidity of surgery, chemoradiation was the treatment resorted to. There are reports in literature, which support the chemotherapy as successful mode of treatment [14,15]. Besides having some radiation mucositis the patient is doing fi ne after ten months of treatment.…”
Section: Discussionmentioning
confidence: 89%
“…SS consistently bears a t(X;18) chromosomal translocation, which produces 1 of 3 possible fusion oncogenes: SS18-SSX1, SS18-SSX2, or SS18-SSX4 (2). No additional consistent genomic perturbations have been identified by profiling, suggesting that the fusion oncogene can drive transformation independently (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have attempted to identify molecular markers of prognostic significance. It has been shown that the over-expression of cell cycle regulatory proteins p53, proliferation markers (PCNA, Ki-67), and aneuploid DNA content are associated with reduced survival of patients with synovial sarcomas [4,5,6,7,8,9,10,11]. To our knowledge, the role of other molecular markers, such as epidermal growth factor receptor (EGFR) and Her2/neu (c-erbB-2), has been previously evaluated only in heterogeneous groups of soft tissue tumors that included very limited numbers of synovial sarcomas [12,13,14].…”
Section: Introductionmentioning
confidence: 99%